Developing a Fair Use Framework for AI-Generated Content in Pakistani Copyright Law: A Doctrinal Legal Analysis - Arshad Nawaz Khan,; Dr. Bahadar Ali,; Farwa Nawaz, (Journal of Peace, Development and Communication, 2024)
In the rapidly evolving landscape of intellectual property rights law the intersection of artificial intelligence and copyright presents extraordinary challenges and opportunities. Current research paper conducts a comprehensive doctrinal legal analysis to develop a fair use framework of AI generated compatible with the socio-economic context of Pakistan. Applying W. P. Saunders' Research Onion layers methodology, Positivism has been selected as philosophy. The doctrinal research design has been based on comprehensive assessment of legal doctrines, statutes, principles of other legal systems, case law, academic research and reports. The chronological horizon spans historical perspectives of copy right law. Primary data collection involves a thorough analysis of legal documents. The study compressively analyzes the practical challenges and opportunities associated with implementing a fair use framework for AI-generated content in Pakistan.